Development of vine rootstock in intercropped with soil cover crops - Queiroz, Gustavo Reis Silva dos Santos (2021)
The use of soil cover crops in the cultivation of the vine is an important technique, especially for tropical climate regions due to high air and soil temperatures. Therefore, this work aimed to evaluate the development of the vine rootstock cultivar “IAC 572 ‘Jales’, intercropped with different types of soil cover plants in the Brazilian Cerrado. The experiment was conducted in an experimental area at the State University of Mato Grosso do Sul - Cassilândia University Unit. The experimental design performed on randomized blocks and with five replications of two rootstock plants, totaling ten useful plants per treatment. The treatments were defined by cover crops: millet (Pennisetum glaucum); crotalaria (Crotalaria juncea); and castor (Ricinus communis). Plant height, stem diameter, number of branches and relative chlorophyll content were evaluated. The development of IAC 572 'Jales' rootstock is favored by the intercropping with crotalaria and millet between the planting rows, as it contributes to greater plant height and higher relative chlorophyll content. The use of castor bean culture, in consortium with the rootstock, should be avoided. These results demonstrate the importance of knowing the interaction between the cultivated species and the ground cover crops.